Developed power quality monitor used for shunt active power filter studies - Pinto, J. G. (2007)
This paper presents a developed Power Quality Monitor used to perform studies in a prototype of a three-phase four wire Shunt Active Power Filter. In the developed equipment, the voltage measurements are made through Hall-effect sensors and for the current measurements flexible Rogowski Coil sensors are used. A conditioning circuit is used to interface the data from the sensors to a standard data acquisition board. The monitoring software was developed in LabVIEW™ that allows the applications to run on Windows in a regular PC. The developed system acquires the data continuously, and stores the desired events in the hard disk. In the case described in this paper, the Power Quality Monitor allows to simultaneously measure the three phase voltages of the power system and four currents, which can be from the source, from the load or from the output of the Shunt Active Filter.